Preferential flow in soils is key to the development of nebkhas in water limited regions - Weicheng Luo; Wenzhi Zhao; Ning An; Chengpeng Sun; Hong Zhou (Geoderma)
Nebkhas, a typical landscape form in arid and semiarid environments, play important roles in desertification control and biodiversity protection. However, water use strategies and infiltration characteristics of nebkhas change with their development stages in regions with low precipitation and deep groundwater, and those changes are not well known. Here, we investigated changes in soil properties and quantified preferential flow characteristics with a dye tracer experiment in nebkhas at different development stages including bare sand dunes (BD), and small (SN) and large nebkha (LN) in different precipitation conditions. Our results showed that soil properties such as clay and silt content, organic carbon content, total porosity, and soil crust thickness increased with nebkha development stages (BD < SN < LN), indicating that soils in LN had better soil structure and physicochemical properties than those in BD. The degree of preferential flow was highest in LN, intermediate in SN, and minimal in BD, and it decreased with an increase in precipitation. Infiltration patterns in SN and LN were dominated by preferential flow, while matrix flow dominated in BD. Higher soil organic matter content, total porosity, and thickness of the soil crust in LN all significantly contributed to the development of preferential flow in nebkhas especially under low precipitation conditions. We conclude that a higher degree of preferential flow in nebkhas may enhance their rainwater infiltration capacity and that represents a very important strategy in nebkha adaptation to extremely arid environments.